Metode Pembinaan Karakter Islami Anak Autis Berbasis Media Audiovisual - Tasbih, Tasbih; A. Hafid, Saidah (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2024)
This study investigates an Islamic character education method for children with autism based on audiovisual media at the Athirah 2 Islamic Elementary School in Makassar. The research was descriptive and qualitative. The data were obtained through observations, interviews, and relevant references. The data sources were School Principal and Vice Principal, Islamic Religion Teacher, and Class Assistant Teacher. The study was conducted between January and May 2024. The data analysis was conducted through data reduction and presentation, and conclusions were drawn. The results of the study show that the Islamic moral education method for autistic children through inclusive-based audiovisual media has proven effective. A notable finding is that the use of audiovisual technology, such as smartphones, is very helpful for the learning process. The implication of the research is that in providing guidance services for autistic children, it is necessary to develop strategies that are tailored to the child's condition based on assessment results.